Influence of Mobile Marketing in Capturing Consumers in the Era of Increasing Smartphone Usage - Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Wayan Suartini; Nurul Yaqin; Kaharuddin; Veronika Yuni T (Politeknik Ganesha Medan, 2023)
In recent years, the use of smartphones has experienced significant growth. Modern society heavily relies on smartphones for various purposes, including communication, accessing information, shopping, and more. This research aims to analyze the impact of mobile marketing in capturing consumers in the era of increasing smartphone usage. The study adopts a qualitative literature review method with a focus on data obtained from Google Scholar spanning the years 2007 to 2023. The study's findings indicate that in an era where smartphone usage is widespread, mobile marketing has proven itself as one of the most effective marketing tools for capturing consumers. Consumer behavior transformation, the power of mobile applications, content personalization, location responsiveness—all are key elements shaping the positive influence of mobile marketing in the business world. Its ability to reach consumers on a personal level, leverage location technology, and provide relevant experiences has opened new opportunities and transformed the marketing landscape as a whole.